The Influence of Internal Audit Effectiveness in Using Information Technology to Improve Audit Quality - Meilani, Avivah; Tifani, Mutiara; Wijaya, Nela Nafilah; Rosnidah, Ida (Rescollacom (Research Collaborations Community), 2025)
This study aims to examine the effect of internal audit effectiveness on audit quality with the use of information technology as an intervening variable. This study is motivated by the importance of the role of internal auditors in ensuring accountable governance, as well as the increasing need for IT in the audit process in this digitalization era. The data analysis technique used is path analysis with a quantitative approach, and the mediation test using the Sobel test. The results of this study indicate that internal audit effectiveness affects audit quality with the use of information technology, this finding shows that information technology plays an important role in strengthening the impact of internal audit effectiveness on the quality of the resulting audit.